Montecarlo Simulation of Two Component Aerosol Processes - Ignacio Huertas, Jose (IntechOpen, 2016)
Nanophase materials are single-phase or multiphase polycrystals, with dimensions of the order of 1-100 nm. As grain size decreases down to the nanometer-size range, nanophase metals generally get stronger and harder, while nanophase ceramics show ductility, even superplasticity, at lower temperatures than conventional brittle ceramics. This book describes a novel method for the production of high purity, unagglomerated nano-particulates of tungsten and tungsten titanium alloys by flame synthesis. W-Ti nano-sized alloys have a combination of high strength (800-1000 MPa), high ductility (10-30%), good e1ectrical and thermal conductivity, corrosion resistance, and excellent machinability. Current applications for W and W-Ti inc1ude radiation shields, lighting components, ignition electrode materials, catalysts in the chemical industry, alloying elements for high speed steels, sputter targets in VLSI chip technology, and sport related parts.